Computing Optimal Interfacial Structure of Modulated Phases (Communications in Computational Physics, 2018)
We propose a general framework of computing interfacial structures betweentwo modulated phases. Specifically we propose to use a computational boxconsisting of two half spaces, each occupied by a modulated phase with given positionand orientation. The boundary conditions and basis functions are chosen to becommensurate with the bulk phases. We observe that the ordered nature of modulatedstructures stabilizes the interface, which enables us to obtain optimal interfacialstructures by searching local minima of the free energy landscape. The framework isapplied to the Landau-Brazovskii model to investigate interfaces between modulatedphases with different relative positions and orientations. Several types of novel complexinterfacial structures emerge from the calculations.